2016
DOI: 10.1038/hdy.2015.114
|View full text |Cite
|
Sign up to set email alerts
|

Linkage mapping of a polymorphic plumage locus associated with intermorph incompatibility in the Gouldian finch (Erythrura gouldiae)

Abstract: Colour polymorphism is known to facilitate speciation but the genetic basis of animal pigmentation and how colour polymorphisms contribute to speciation is poorly understood. Restricted recombination may promote linkage disequilibrium between the colour locus and incompatibility genes. Genomic rearrangement and the position of relevant loci within a chromosome are important factors that influence the frequency of recombination. Therefore, it is important to know the position of the colour locus, gene order and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…Orange individuals are thus identical to red individuals at the Red locus, but express a different complement of carotenoids in their masks [19]. Recently, the Red locus was mapped to an approximately 7.2 cM interval on the Z chromosome using microsatellite markers [20]. However, the resolution of this mapping did not allow for the identification of the gene(s) and causal variants underlying this polymorphism.…”
Section: Introductionmentioning
confidence: 99%
“…Orange individuals are thus identical to red individuals at the Red locus, but express a different complement of carotenoids in their masks [19]. Recently, the Red locus was mapped to an approximately 7.2 cM interval on the Z chromosome using microsatellite markers [20]. However, the resolution of this mapping did not allow for the identification of the gene(s) and causal variants underlying this polymorphism.…”
Section: Introductionmentioning
confidence: 99%
“…By using high-depth / low SNP density RADSeq 20 and low-depth / high SNP density whole-genome sequencing (see Methods), we identified a region on the Z chromosome strongly associated with redblack head colouration (1,000 permutations, P < 0.05, Fig. 1a, Supplementary Figures 1 and 2) within 4 the candidate interval identified in a previous linkage analysis 21 . The genotypes of the wild birds (n male = 89, n female = 72) from an allele-specific PCR in this region showed a near-perfect association with head colour, with one exception, in a female (Fisher's exact test, male: P < 10 -15 ; female: P = 7.52 × 10 -10 , Fig.…”
Section: Identification Of the Red Locusmentioning
confidence: 88%
“…Centromeres and genomic rearrangements, particularly chromosomal inversions, may reduce recombination rates and generate significant LD blocks between haplotypes 22 . However, our previous work showed that the Red locus is not located near the centromere or in a large genomic rearrangement between morphs 21 . We confirmed this finding with a fine-scale test for inversion breakpoints using long-range PCR: our genomic assembly across the Red locus for each genotype 5 contained contiguous homologous sequence, consistent with the absence of an inversion differentiating the Z R and Z r alleles ( Fig.…”
Section: High Ld But No Genomic Rearrangements Around the Red Locusmentioning
confidence: 91%
See 2 more Smart Citations